Kolaborasi ICRAF dan Masyarakat melalui Proyek Land4Lives untuk Mendorong Pembangunan Berkelanjutan di Sulawesi Selatan - Rusdi, Besse Fadhilah (Kolaborasi Masyarakat, 2025)
This study aims to analyze the implementation of sustainable development values by the World Agroforestry Centre (ICRAF) through the Land4Lives project in South Sulawesi. The research focuses on examining ICRAF’s roles as an implementer, catalyst, and partner, as well as the impacts experienced by the community in Pakkasalo Village, Bone Regency. The research method used is descriptive qualitative, with primary data obtained through interviews with ICRAF staff and local community members, and secondary data collected from documents, journals, and reports. The results indicate that ICRAF acts as an implementer through the Land4Lives program, the Young Landscape Researchers Incubator (IPML), village-level food and nutrition security campaign initiatives, and the siALAM website service. As a catalyst, ICRAF fosters innovation through LUMENS and various innovative financing schemes. As a partner, ICRAF collaborates with local governments in assisting the preparation of Green Economic Growth Master Plans. The impacts experienced by the community of Pakkasalo Village include enhanced climate adaptation capacity through land management programs and strengthened food security. Overall, this study highlights the importance of synergy between international NGOs, local governments, and communities in achieving sustainable development.